Sosialisasi Pneumonia Nosokomial: Tantangan Diagnostik dan Terapi di Rumah Sakit - Hapsah, Hapsah (Medan Resource Center, 2025)
Nosocomial pneumonia is a prevalent infection in hospitals that poses significant challenges in diagnosis, therapy, and healthcare equity. This study employed a descriptive qualitative approach to explore the social, clinical, and policy factors influencing the management of nosocomial pneumonia in two hospitals in Jakarta. Data were collected through interviews, observations, and documentation, subsequently analyzed thematically. The findings reveal diagnostic delays due to nonspecific symptoms and limited facilities, as well as high levels of antimicrobial resistance among key pathogens. Disparities in facilities across different care classes increase infection risks for lower-class patients. Furthermore, adherence to infection prevention protocols remains suboptimal. The management of nosocomial pneumonia requires an interdisciplinary approach and comprehensive transformation of hospital care systems to address these complex medical and social challenges.